1999
DOI: 10.1002/(sici)1097-0185(19990501)255:1<34::aid-ar5>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural specializations of the eye in the vizcacha (Lagostomus maximus maximus)

Abstract: Vizcachas (Lagostomus maximus maximus, Chinchillidae) are nocturnal rodents living in burrows in many regions of Argentina, Bolivia, and Chile. We have studied the eye of the vizcacha using several light and electron microscopic procedures, with the purpose of understanding the role of vision in the behavior of this species. Our observations demonstrated an avascular, rod-rich retina, with a specialized region spanning through most of the equator of the eye. In this central band, all neural retinal layers exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previous studies demonstrated that the pineal gland and its hormone, melatonin, are involved in its reproductive rhythmicity (Domínguez et al, 1987;Fuentes et al, 1991;Pelzer et al, 1999;Muñ oz et al, 1999Muñ oz et al, , 2001Mohamed et al, 2000). Lascano et al (1999) demonstrated an avascular, rod-rich retina, with a specialized region spanning through most of the equator of the eye of the viscacha, suggesting that this equatorial region could be a highly sensitive light detector related to foraging behaviors during crepuscular or nocturnal hours.…”
mentioning
confidence: 99%
“…Previous studies demonstrated that the pineal gland and its hormone, melatonin, are involved in its reproductive rhythmicity (Domínguez et al, 1987;Fuentes et al, 1991;Pelzer et al, 1999;Muñ oz et al, 1999Muñ oz et al, , 2001Mohamed et al, 2000). Lascano et al (1999) demonstrated an avascular, rod-rich retina, with a specialized region spanning through most of the equator of the eye of the viscacha, suggesting that this equatorial region could be a highly sensitive light detector related to foraging behaviors during crepuscular or nocturnal hours.…”
mentioning
confidence: 99%
“…Nocturnal animals, which need to see well at night, generally have eyes with wide pupils, large lens, rod-rich retinas and tapetum [11]. The vizcacha has an avascular retina [11] while the rabbit [23] and guinea pig [19] have a partially vascularized retina.…”
Section: Discussionmentioning
confidence: 99%
“…The vizcacha has an avascular retina [11] while the rabbit [23] and guinea pig [19] have a partially vascularized retina. This optical strategy plays a significant role in improving photon capture for greater night vision capabilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations